APLIKASI KOMPOS KOTORAN AYAM UNTUK MENINGKATKAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) DI TANAH MASAM - -, M. TUFAILA; LAKSANA, DEWI DARMA; ALAM, SYAMSU (Jurnal Agroteknos, 2014)
The purpose of this study was to determine the ability of composted chicken manure to improve cucumbers yields in acid soils. The research was conducted in the Bende Village, District of Kadia, Kendari, from October to December 2013. Soil analysis was performed at the Soil Science Unit of Agro Technology Laboratory Faculty of Agriculture, University of Halu Oleo. This study was prepared using randomized block design (RBD) with a single factor of chicken manure compost treatment, consisting of 6 levels and repeated four times. The treatments were : without composted chicken manure (D0), manure dose of 5 ton ha-1 (D1), manure dose 10 tons ha-1 (D2), manure dose of 15 tons ha-1 (D3), manure dose of 20 tons ha-1 (D4) and manure dose of 25 tons ha-1 (D5). Observed variables included: growth and crop production, analysis of soil chemical properties, as well as the analysis of the quality of the fertilizer used. Data were analyzed using analysis of variance followed by Duncan's Multiple Range Test. The results showed that the use of chicken manure compost at a dose of 15 tons ha-1 (D3) gave the best effect on the growth and yield of cucumber in acid soils. Keywords: acid soi,l chicken manure compost, cucumber crop